2017
DOI: 10.7554/elife.21792
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate cross-frequency coupling via generalized eigendecomposition

Abstract: This paper presents a new framework for analyzing cross-frequency coupling in multichannel electrophysiological recordings. The generalized eigendecomposition-based cross-frequency coupling framework (gedCFC) is inspired by source-separation algorithms combined with dynamics of mesoscopic neurophysiological processes. It is unaffected by factors that confound traditional CFC methods—such as non-stationarities, non-sinusoidality, and non-uniform phase angle distributions—attractive properties considering that b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 68 publications
0
53
0
1
Order By: Relevance
“…The resulting component time-series is then the row vector y on which all subsequent analyses can be performed. This spatial filter method has the advantage of increasing signal-to-noise ratio, taking into account inter-individual topographical differences, and avoiding electrode selection bias (Nikulin et al, 2011;Cohen, 2017).…”
Section: Spatial Filtering Of the Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting component time-series is then the row vector y on which all subsequent analyses can be performed. This spatial filter method has the advantage of increasing signal-to-noise ratio, taking into account inter-individual topographical differences, and avoiding electrode selection bias (Nikulin et al, 2011;Cohen, 2017).…”
Section: Spatial Filtering Of the Datamentioning
confidence: 99%
“…In order to increase the signal-to-noise ratio, to avoid bias in electrode selection, and to account for variability in subject's topography, we chose to apply a multivariate guided source separation method, namely, generalized-eigen-decomposition (Nikulin et al, 2011;de Cheveigné and Arzounian, 2015). This method allows to create a single component that best reflects target features of the signal (in this case, a narrow-band frequency-specific signal) and has been shown to be very helpful in maximizing low-frequency features in the EEG signal (Cohen, 2017). Our results showed that this method successfully isolated different narrowband frequency-specific components.…”
Section: Unmixing Frequency-specific Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an active field, new CFC metrics are continuously being elaborated; there are certainly far more CFC metrics than the ones summarized in this chapter. Important advances include metrics designed to infer coupling directionality (Paluš 2014;Jiang et al 2015;Li et al 2016), to improve time-resolution (Voytek et al 2013;Dvorak and Fenton 2014;Samiee and Baillet 2017), to provide confidence intervals and higher statistical rigor (Kramer and Eden 2013;van Wijk et al 2015), to avoid standard filters by using autoregressive models (Tour et al 2017) or empirical mode decomposition (Pittman-Polletta et al 2014), and to cope with multiple channel data and spatial filtering (Cohen 2017).…”
Section: Novel Cfc Metricsmentioning
confidence: 99%
“…While most of the multivariate source-separation methods focus on the extraction of independent sources (e.g. independent component analysis -ICA), there are only a few studies utilizing multivariate methods to extract dependent sources from the electrophysiological recordings of the human brain (Chella et al;Cohen, 2017;Dähne et al, 2014;Nikulin et al, 2012;Volk et al, 2018). These methods optimize a contrast function of the desired type of coupling.…”
Section: Introductionmentioning
confidence: 99%